Synthesis and characterization of supported copper-based catalysts for thermo-catalytic hydrogenation of carbon dioxide into methanol - Duma, Zama Gift (My University, 2022)
The abatement of anthropogenic sources of carbon dioxide (CO2) requires carbon capture and utilisation technologies which are innovative. The storage of green hydrogen (H2) in methanol is a viable route to utilise captured CO2. The thermocatalytic hydrogenation of CO2 to green methanol and/or other value-added chemicals using heterogenous catalysts presents an alternative, sustainable opportunity towards carbon neutrality. The valorisation of CO2 aims to offset the deleterious effects of greenhouse gas emissions which have already sparked global warming and climate change. This study reports the use of heterogeneous copper-based catalysts supported on metalorganic frameworks (MOFs) for the thermocatalytic hydrogenation of CO2 to methanol. Zirconium-based UiO-66 and aluminium fumarate MOF (AlFum MOF) were selected as supports due to their desirable physicochemical properties such as high surface area, pore-volume, and relatively high thermal stability. Copper-based catalysts were prepared via a co-precipitation process, to form Cu/ZnO/Al2O3/MgO (CZA) catalysts that had a similar elemental composition to a commercial-grade catalyst, and slurry phase impregnation was utilised to yield bimetallic Cu-ZnO MOF-supported catalysts. The Mg-promoted CZA catalyst prepared in this work had relatively larger CuO crystallites of 7.2 nm compared to 5.2 nm in the commercial catalyst. The latter also exhibited a larger specific surface area of 96.7 m2 /g compared to 37.9 m2 /g which is attributed to the difference in average crystallite size. In addition, despite the discrepancy in physicochemical properties, the CO2 conversions and methanol selectivity of the Mg-promoted CZA catalyst were found to be 30.8% and 24.2% compared to 28.9% and 15% in the commercial catalyst, respectively. Cu and Zn were supported on zirconium-based UiO-66 and AlFum MOFs via slurry phase impregnation. The crystallinity, specific surface area, and pore volume of MOFsupports were observed to decrease after metal loading and thermal activation of the catalyst precursors. The MOF-supported catalysts exhibited CO2 conversions ranging from 0-45.6% and methanol selectivity of up to 15.7%. The Cu/ZnO/UiO-66 exhibited the greatest methanol productivity of 128 gMeOH/Kgcat/h compared to 51.8 gMeOH/Kgcat/h in the commercial catalyst. All the MOF-supported catalysts exhibited stability within v the 24-hour evaluation period where equilibrium CO2 conversions were reached within 1-2 hours.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: Copper-based catalysts; Thermo-catalytic hydrogenation; Methanol